TOWARDS AN ATTENTION-BASED VIEW OF THE FIRM - OCASIO, WILLIAM (Strategic Management Journal, 1997)
The central argument is that firm behavior is the result of how firms channel and distribute the attention of their decision-makers. What decision-makers do depends on what issues and answers they focus their attention on. What issues and answers they focus on depends on the specific situation and on how the firm’s rules, resources, and relationships distribute various issues, answers, and decision-makers into specific communications and procedures. The paper develops these theoretical principles into a model of firm behavior and presents its implications for explaining firm behavior and adaptation. © 1997 by John Wiley & Sons, Ltd.